SUICIDAL IDEATION AMONG OUT-OF-SCHOOL ADOLESCENTS IN NIGERIA: IMPLICATIONS FOR EDUCATIONAL AND MENTAL HEALTH REFORMS - Animba, Ijeoma Evelyn; Osim, Happiness Ukamaka; Ezema, Edith Obianuju (Journal of Continuing and Development Education, 2025)
This paper investigated relationship between personality traits and suicidal ideation among out-of-school adolescents in Nigeria. Data from different scholars and researchers in Nigeria and outside Nigeria was used in critical dissection of the problem under study. Education is the foundation and instrument for social change in any society. No nation develops educationally, economically and mentally when her young adolescents battle with suicidal ideation and suicide. According to UNICEF, one in four young Nigerian adolescents is prone to suicide, hence; need for total overhaul in the nation’s education and mental health care in order to arrest the problem. The menace of out-of- school is becoming worrisome as Nigerian policy is not yet ready to address it. This explains the reasons her educational policy is still a national discourse with undoubtedly a number of significant impediments in the last decade as it continues to struggle with implementation and assurance of quality educational policy. This paper therefore; x-rayed suicidal ideation among out-of-school adolescents in Nigeria. It also investigated the need to use education in dealing with suicidal issues from cradle of adolescence, given to the fact that suicide and suicidal ideation is common among young people especially out-of-school adolescents. Using secondary sources of data and different research views across the world, highlight was given on suicidal ideation amongst out-of- school adolescents can be tackled through comprehensive education and mental health reforms. It was recommended among others for a total overhaul of the educational policy embedded in critical thinking in order to handle suicidal ideation among adolescents.